Intensification of student creative activity at choral conducting classes - Teriaieva, Larisa (Educological discourse, 2022)
Modern national education is aimed at improving the quality of training musical art teachers-to-be, self-improvement of the professional and methodological competence of teachers and students, enhancing their creative activity, practical The purpose of this article is a purposeful search and selection of principles, methods and forms of education that contribute to the activation of student creative activity, the development of their creative thinking, imagination and fantasy. The article reflects the features of choral conducting classes based on the principle of interdisciplinary connections; different methods, forms and innovative principles of activating creative activity of students are offered; game methods of training are considered and examples of musical tasks for development of creative abilities of students are presented. At choral conducting classes, it is advisable to use innovative principles for the creative development of students, namely: the principle of individual abilities for choral conducting; interdisciplinary connections of choral conducting with other disciplines; interactive learning; innovative visibility; creative development, as well as special musical methods, methods of cognitive activity and others. The musical and creative games proposed in this article aim to activate the attention and thinking of specialists-to-be, to contribute to the creation of their own interpretation of choral works, to intensify their mental activity, musical memory, to expand the knowledge of specialists-to-be about vocal and choral terminology, to deepen the theoretical knowledge of students about the authors of choral works, to highlight the performing activities of famous modern choirs. During the games, students are invited to demonstrate the expressive playing of the choral score on the piano, show their ability to transpose the melody into a convenient vocal range and arrange choral works, create their own vocal and choral exercises and songs for students.